1.(a-b)(a+b)-(a+b)²+2b(b-a),化简2.设a-b=2,求a²+b²/2-ab的值3.计算.[(2x-y)(2x+y)+y(y-6x)]÷2x4.化简:(a+b)(a-b)+(a+b)²-2a²

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/13 20:25:06
1.(a-b)(a+b)-(a+b)²+2b(b-a),化简2.设a-b=2,求a²+b²/2-ab的值3.计算.[(2x-y)(2x+y)+y(y-6x)]÷2x4.化简:(a+b)(a-b)+(a+b)²-2a²

1.(a-b)(a+b)-(a+b)²+2b(b-a),化简2.设a-b=2,求a²+b²/2-ab的值3.计算.[(2x-y)(2x+y)+y(y-6x)]÷2x4.化简:(a+b)(a-b)+(a+b)²-2a²
1.(a-b)(a+b)-(a+b)²+2b(b-a),化简
2.设a-b=2,求a²+b²/2-ab的值
3.计算.[(2x-y)(2x+y)+y(y-6x)]÷2x
4.化简:(a+b)(a-b)+(a+b)²-2a²

1.(a-b)(a+b)-(a+b)²+2b(b-a),化简2.设a-b=2,求a²+b²/2-ab的值3.计算.[(2x-y)(2x+y)+y(y-6x)]÷2x4.化简:(a+b)(a-b)+(a+b)²-2a²
1、-4ab,
2、=(a-b)^2/2+a^2/2=2+a^2/2>=2.所以是大于等于2.
3、2x-3y
4、2ab

1. -4ab
2. 2+a²/2
3. 2x-3y
4. 2ab

a-b+(a+b)2+b2-a